What determines executives' remuneration in Malaysian public listed companies? - Ghasemi, Maziar; Ab Razak, Nazrul Hisyam (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
Most studies of the determination of executive compensation mainly focus on the Chief Executive Officer (CEO) compensation. However, determination of executives’ compensation is relatively ignored in the literature. This paper examines the impact of executives’ ownership, firm performance, board size and its components, as well as some other financial factors, on executives’ compensation in the context of Malaysia as an emerging economy. The data from 267 firms during 2006-2014 in the main market of Bursa Malaysia has been used. This paper finds that firm performance, leverage and number of non-executive directors have negative effects on executives’ compensation. Conversely, dividends, percentage of executives’ directors, board size and size of firms have positive effects on executives’ compensation. There is no evidence that executives’ ownership has significant effects on their compensation. From the viewpoint of the agency theory about the effects of larger boards, firm profitability, and executive percentage on executives’ compensation, it is perceived that the weak governance exists among listed companies in the Malaysian market. Considering the power of concentrated ownership in Malaysia, the insignificant impact of executives’ ownership on their remuneration is an important finding of this research.